2021
DOI: 10.7717/peerj-cs.375
|View full text |Cite
|
Sign up to set email alerts
|

OPTICAL+: a frequency-based deep learning scheme for recognizing brain wave signals

Abstract: A human–computer interaction (HCI) system can be used to detect different categories of the brain wave signals that can be beneficial for neurorehabilitation, seizure detection and sleep stage classification. Research on developing HCI systems using brain wave signals has progressed a lot over the years. However, real-time implementation, computational complexity and accuracy are still a concern. In this work, we address the problem of selecting the appropriate filtering frequency band while also achieving a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…To demonstrate the validity of the proposed framework, we applied the proposed framework (LMD-CSP and MOGWO-TWSVM) and other recent methods such as the temporal filter parameter optimization with CSP (TFPO-CSP) ( Kumar & Sharma, 2018 ) and the frequency-based deep learning scheme for recognizing brain wave signals (OPTICAL+) ( Kumar, Sharma & Sharma, 2021 ) on the same data sets, this data sets include the EEG data of shoulder abduction and extension. The obtained results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the validity of the proposed framework, we applied the proposed framework (LMD-CSP and MOGWO-TWSVM) and other recent methods such as the temporal filter parameter optimization with CSP (TFPO-CSP) ( Kumar & Sharma, 2018 ) and the frequency-based deep learning scheme for recognizing brain wave signals (OPTICAL+) ( Kumar, Sharma & Sharma, 2021 ) on the same data sets, this data sets include the EEG data of shoulder abduction and extension. The obtained results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…That study reported an average error recognition rate of 10.19% on BCI Competition III Dataset IVa (right hand and foot). Recently, Kumar, Sharma & Sharma (2021) used genetic algorithm (GA) for adaptive filtering, combined CSP and long short-term memory network (LSTM) for feature extraction, and applied SVM for classification. It should be noted that these studies focused on binary problems.…”
Section: Introdctionmentioning
confidence: 99%
“…In recent years, there has been a surge in the use of deep learning techniques for MI-EEG classification tasks. Researchers have introduced various deep learning network models, including Convolutional Neural Networks (CNNs) (Zhang et al, 2020 ), Recurrent Neural Networks (RNNs) (Luo et al, 2018 ; Kumar et al, 2021 ), Deep Belief Networks (DBNs) (Xu et al, 2020 ), and Autoencoder (AE) structures (Hassanpour et al, 2019 ). Among these models, CNNs have been widely adopted, and a variety of CNN network designs have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Sakhavi et al built a classification model with CNN [7] . Kumar et al presented a model that employs a long short-term memory (LSTM) network [8] . In general, CNN has demonstrated superior performance than the recurrent neural network (RNN) and DBN in this field [5] .…”
Section: Introductionmentioning
confidence: 99%